Cover Image. (17th March 2020) - Wang, Lu; Yao, Shaobo; Tang, Ruikun; Zhu, Honghao; Zhang, Lingling; Gong, Jian; Chen, Qiusong; Collier, Thomas Lee; Xu, Hao; Liang, Steven H.
Abstract : The cover image is based on the Research Article A concisely automated synthesis of TSPO radiotracer [18F]FDPA based on spirocyclic iodonium ylide method and validation for human use by Lu Wang et al., https://doi.org/10.1002/jlcr.3824 .